(untitled) (CIPEEX, 2022)
GERIATRIC DEPRESSION IS A MULTIFACTORIAL DISEASE OF GREAT INCIDENCE. NEVERTHELESS, IT IS POSSIBLE TO OBSERVE A DEVALUATION AND, CONSEQUENTLY, AN UNDERDIAGNOSIS OF THIS DISEASE. IN THE MEANTIME, PAYING ATTENTION TO THE TOPIC WITH THE INVESTIGATION OF THE FACTORS ASSOCIATED WITH DEPRESSION IN THE THIRD AGE IS ESSENTIAL FOR CHANGING THE CURRENT UNPROMISING PICTURE. IN VIEW OF THIS, THE WORK AIMS TO DESCRIBE THE BIOLOGICAL, PSYCHOLOGICAL AND SOCIAL FACTORS ASSOCIATED WITH THE DEVELOPMENT PROCESS AND AGGRAVATION OF GERIATRIC DEPRESSION. THIS IS AN EXPANDED ABSTRACT FROM THE PUBMED, SCIENCEDIRECT, REDALYC, ELSEVIER, OVID AND COCHRANE DATABASES, SELECTING 12 ARTICLES BETWEEN 2016 AND 2018 THAT FIT THE THEME AND DESCRIPTORS. THE RESULT FOUND WAS THAT, GENERALLY, THE DEPRESSIVE ELDERLY PRESENTED THE PROFILE OF BEING FEMALE, OF LOW SCHOOLING, WITH LOW LEVELS OF VITAMIN D CORPORAL, HABITS OF LIFE THAT INVOLVE THE INGESTION OF ALCOHOLIC BEVERAGE, SMOKE AND SEDENTARISM, BESIDES TRAUMAS IN THE CHILDHOOD, LIVING ALONE OR IN NURSING HOMES AND OTHER PHYSIOLOGICAL DISORDERS. THUS, IT IS CONCLUDED THAT THE UNDERSTANDING OF THE VARIOUS FACTORS ASSOCIATED WITH DEPRESSION IN THE THIRD AGE HELPS TO COMBAT THE UNDERVALUATION OF COMORBIDITY.